ANALISIS MISKONSEPSI SISWA MENGGUNAKAN INSTRUMEN FOUR-TIER DIAGNOSTIC TEST PADA MATERI EKSPONEN DITINJAU DARI TINGKAT KECEMASAN MATEMATIKA - Axcelleosa Gloria Setiawan; Samijo; Bambang Agus Sulistiyono (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the misconceptions of grade X students at SMKN 3 Kediri on exponential material using the Four-Tier Diagnostic Test instrument, viewed from mathematics anxiety levels (low, moderate, and high). The research employed a descriptive qualitative approach to obtain an in-depth understanding of students’ thinking processes and conceptual understanding. The subjects of this study were 29 students of class X Desain dan Produksi Busana 3 at SMKN 3 Kediri who had previously studied exponential material. Data were collected using a Four-Tier Diagnostic Test to identify students’ conceptual understanding and misconceptions, and a Mathematics Anxiety Scale (SKMS) to determine their level of mathematics anxiety. The combination of these instruments allows for a more comprehensive analysis of cognitive and affective factors influencing students’ learning outcomes. The analysis of misconceptions was conducted based on four-tier response patterns, which classify students into categories of understanding, lack of knowledge, and misconceptions. The types of misconceptions identified include generalization errors, notation errors, specialization errors, and language-related misconceptions. Each type reflects different forms of conceptual misunderstanding in exponential material, such as incorrect application of exponent rules or misinterpretation of mathematical symbols and language. The findings of this study are expected to provide a detailed and comprehensive picture of students’ misconception patterns in relation to their mathematics anxiety levels. Furthermore, the results are intended to serve as a reference for teachers in designing more effective, adaptive, and student-centered instructional strategies, particularly in addressing misconceptions in exponential topics within vocational high school contexts.